2017
DOI: 10.2147/idr.s126209
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility profile, treatment outcome and serotype distribution of clinical isolates of <em>Salmonella enterica</em> subspecies <em>enterica</em>: a 2-year study from Kerala, South India

Abstract: Background/purposeTyphoid and paratyphoid fever continue to be important causes of illness and death in parts of Asia, being associated with poor sanitation and consumption of unsafe food and water. Antimicrobial resistance has emerged to traditional first-line drugs, namely, the fluoroquinolones, as well as to third-generation cephalosporins, posing challenges to treatment. Azithromycin has proven to be an effective alternative for treatment of uncomplicated typhoid fever. The purpose of this study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…A total of 109 articles were included for analysis. 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94...…”
Section: Resultsunclassified
“…A total of 109 articles were included for analysis. 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94...…”
Section: Resultsunclassified
“…Thirty two (Fig. 1)studies (Table II)9101112131415161718192021222324252627282930313233343536 satisfied the inclusion criteria from which 49 yr-stratified summaries of S. Typhi antimicrobial-resistant isolates were obtained. For instance, Gautam et al 15 reported the isolates of their study in a year-stratified manner for five years, therefore providing five serial year-stratified summaries.…”
Section: Resultsmentioning
confidence: 99%
“…A Bangladeshi study 16 also reported 100% susceptibility to cefixime and ceftriaxone. A study in India was also reported 100% susceptibility to ceftriaxone 17 .…”
Section: Resultsmentioning
confidence: 95%